PERANCANGAN KAMPANYE SOSIAL BUKU ILUSTRASI MOTIVASI PENCEGAHAN KECENDRUNGAN GANGGUAN MENTAL REMAJA - Raia, Divanna Hikary; Damarjati, Fx. (Jurnal Industri Kreatif dan Inovatif, 2024)
The issue of adolescent mental health has become a serious concern in many countries. To address this issue, there is a need for a creative and effective approach to deliver motivational messages that can prevent tendencies toward mental disorders in adolescents. One proposed solution is to use motivational illustration books as a means to provide inspiration, motivation, and psychological support to teenagers. The research method approach used is descriptive qualitative by collecting data from sources and then analyzing it to become visual material. This social campaign aims to promote the use of motivational illustration books as a tool for preventing adolescent mental disorders. In designing this campaign, various theories of visual communication design will be employed, including layout, color, illustration, and typography, to create engaging, inspirational, and easily understandable messages for teenagers. The campaign design focuses more on the publication of motivational illustration books that can be widely accessed by teenagers. The content of these books will be structured in such a way that it is relevant to the issues commonly faced by teenagers in dealing with mental disorders. Thus, these books are expected to serve as a source of inspiration and motivation for teenagers in overcoming various challenges they may encounter.